The pearl that broke its shell : a novel - Hashimi, Nadia (William Morrow, 2014)
In Kabul, 2007, with a drug-addicted father and no brothers, Rahima and her sisters can only sporadically attend school and rarely leave the house, and their only hope lies in the ancient custom of bacha posh, which allows young Rahima to dress and be treated as a boy until she is of marriageable age.